2015
DOI: 10.1037/cns0000049
|View full text |Cite
|
Sign up to set email alerts
|

All in one fell Stroop: Examining consciousness thresholds with a multiple response paradigm.

Abstract: We test a novel multiple response paradigm for establishing objective and subjective thresholds of consciousness using the Stroop task. Replicating the threshold-defined qualitative differences originally reported by Cheesman and Merikle (1984, 1986), this paradigm also addresses trial-by-trial fluctuation in thresholds of objective and subjective thresholds. On each trial, suprathreshold was indicated by correct alternative-forced-choice (AFC) word identification and reporting word readability, subjective thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…However, the shorter prime durations lack significant Stroop effects, which is in contrast to the results from emotional Stroop studies performed with subliminal stimuli. This overall pattern is, however, consistent with studies based upon traditional Stroop color words: Stroop effects are only obtained when participants can show some measurable behavioral sensitivity to the prime stimuli (Cheesman & Merikle, 1984, 1986; Kouider & Dupoux, 2004; Lorentz et al., 2015; Sand, 2016; Sand & Nilsson, 2017; Severance & Dyer, 1973; Tzelgov et al., 1997).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, the shorter prime durations lack significant Stroop effects, which is in contrast to the results from emotional Stroop studies performed with subliminal stimuli. This overall pattern is, however, consistent with studies based upon traditional Stroop color words: Stroop effects are only obtained when participants can show some measurable behavioral sensitivity to the prime stimuli (Cheesman & Merikle, 1984, 1986; Kouider & Dupoux, 2004; Lorentz et al., 2015; Sand, 2016; Sand & Nilsson, 2017; Severance & Dyer, 1973; Tzelgov et al., 1997).…”
Section: Discussionsupporting
confidence: 84%
“…The null awareness criterion for the stimulus displays in these studies is often described as an objective threshold, such as identification d′ = 0 from a prime stimulus identification task. Most studies have found that no Stroop effect occurs when the display parameters are rigorously set to eliminate all behavioral evidence of sensitivity to the prime words (Cheesman & Merikle, 1984; Kouider & Dupoux, 2004; Lorentz et al., 2015; Severance & Dyer, 1973; Tzelgov, Porat, & Henik, 1997). However, a different finding emerges if the display parameters are relaxed slightly (e.g., longer durations, less masking) to make the prime word stimuli just slightly more visible to the participants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for why Experiment 2 did not demonstrate the same interference may involve inclusion of a congruent condition, although this appears unlikely. Specifically, the inclusion of congruent stimuli, and greater proportions of congruent stimuli relative to incongruent stimuli, generally increase the overall size of the Stroop effect (Cheesman and Merikle, 1986 ; Lorentz et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%